Telehealth Adoption in an Outpatient Oncology Ward: A Best Practice Implementation Project - Filipa Ventura; Helena Domingues; Gisela Almeida; Daniela Cardoso; Rogério Rodrigues; Isabel Moreira; Mariana Pires; Inês Gomes; Rosa Silva; Cláudia Oliveira; Ana Filipa Cardoso; Liliana Ribeiro; et al. (MDPI AG, 2022)
Telehealth is increasingly taking place to support the transition of care and self-management of people living with cancer in outpatient oncology settings. Despite its recognised value, the scientific evidence points to disparities with regard to implementation of telehealth that might compromise the equity of access. Following the Joanna Briggs Institute (JBI) implementation approach, this project aims to promote the implementation of best practice recommendations for telehealth adoption in an outpatient oncology setting. Assisted by the Practical Application of Clinical Evidence System (PACES), the implementation process comprises three phases of (i) a baseline audit, (ii) feedback to the healthcare team and establishment of implementation strategies with the Getting Research into Practice (GRiP) tool, and (iii) a follow-up audit. The project is expected to allow the identification of barriers and facilitators for the implementation of telehealth in outpatient oncology and develop a strategy plan for its adoption, with the involvement of end-users and stakeholders. The successful adoption of telehealth according to the best available evidence will likely enhance equity of access to healthcare and quality of care at a distance.